Towards a sustainable environment: an analysis on courtyards microclimate in the tropical region - Abdul Majid, Noor Hanita; Sapian, Abdul Razak; Denan, Zuraini (2002)
This study is a preliminary attempt to collect information and analyse the microclimate of courtyards in the tropical region. The field experiment undertaken has contributed towards understanding the microclimate characteristics in the outdoor space. Courtyards in IIUM have been selected to represent courtyards in hot humid climate due to extensive application of the courtyard concept in the campus development. The field experiments have indicated the conditions at shaded and non-shaded conditions of the outdoors. The findings from the analysis of the climatic parameters suggested that shaded conditions are most favorable. The data from air temperature, relative humidity and air velocity indicated that the shaded areas can ameliorate the microclimate conditions at the courtyards. It can be also be deduced that courtyards contributed to providing comfortable outdoors that consecutively contributed to sustainable environment. Courtyards can also be an approach adopted to reduce energy consumption by modifying the transitional space between outdoor and indoor.